Mentoring of MGMP ICT High School in East Kotawaringin to Improve Teacher Competence and Preserve Culture through AR and Metaverse Technology in Tumbang Gagu - Minarni; Elika Thea Kirana; Abdul Aziz (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
This community service program is the result of 2023 research aimed at developing Virtual Reality (VR) Metaverse and Augmented Reality (AR) technology to introduce the history and philosophy of the Tumbang Gagu traditional house in Central Kalimantan. This technology was tested in schools in East Kotawaringin (KOTIM) with positive responses from teachers and students. The program aims to enhance teachers' competence in utilizing modern technology for education and the preservation of local culture. The activity stages include socialization, training on the application of technology, mentoring, and continuous evaluation. The results of this program include the creation of AR-based historical storybooks, the publication of scientific articles in SINTA 4 indexed journals, and the introduction of local culture through advanced technology. The program resulted in successful training, with 85% of participants trained, competence increased by 70%, and the quality of AR products reached 60%. MGMP ICT participation increased by 50%. The outputs: posters, videos, publications, and recognition of student credits. This program successfully increased teacher competence and the quality of technology-based learning in the KOTIM region, with positive impacts recognized by mass media and scientific publications.